Effective corrosion inhibition performance of La(NO3)3 doped sol-gel coating on galvanized steel sheet. Issue 6 (28th October 2014) - K. Guin, Akshya; Bhadu, M.; Sinhababu, Mahua; Mundhara, Ankita; Rout, T.K.; Udayabhanu, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this work was to study the effect of La(NO 3 ) 3 on the corrosion behavior of sol-gel coating prepared by hydrolysis of 3-glycidoxypropyl)methyldiethoxysilane and 3-aminopropyltriethoxysilane. Generally, galvanized steel is subjected to a hexavalent chromium passivation treatment. Hexavalent chromium passivation is not an environment friendly product and researchers are looking for a suitable alternative for chromium passivation treatment. Some of the potential alternatives are silicate conversion coating or the use of silane-based coatings. In this context, sol-gel coating was investigated as a potential replacement for hazardous hexavalent chromium passivation treatment. Design/methodology/approach – The sol-gel film was deposited on galvanized steel sheet by the dip coating method. The molecular vibration and chemical properties of sol-gel solution and coated films were obtained by infrared spectroscopy. Images from a scanning electron microscope were obtained to characterize the morphology of the film. The corrosion resistance of the coated samples was evaluated by electrochemical impedance spectroscopy (EIS), potentiodynamic polarization curves and salt spray tests. Findings – The results indicated that La(NO 3 ) 3 -doped coatings were more resistance to corrosion than undoped coating. The coating doped with 0.5 per cent La(NO 3 ) 3 offered improved corrosion protection due to the inhibitive action of the La3+ ion. Originality/value – This result can provide a reference for the development of chromium-free passivation for galvanized sheeting.